READERâS THEATER : A SOLUTION TO IMPROVE READING FLUENCY AND READING COMPREHENSION ACHIEVEMENTS OF EFL STUDENTS - RACHMATIA, MEUTIA (Sriwijaya University Learning and Education International Conference, 2016)
Nowadays, reading is a very essential skill for people since they can obtain information from it. Reading means comprehension since the process of reading is where the readers strive to understand and respond the ideas that are expressed in written text. But at the fact, reading achievement in Indonesia still low based on EF survey in 2013. To solve the problem of Reading Comprehension achievement, the students should focus on Reading Fluency first. Many researchers said that there are a correlation between Reading Fluency and Reading Comprehension. They said that fluency is an important part in reading curriculum, but teachers do not understand it. This article will propose a strategy to improve Reading Fluency and Reading comprehension namely Readerâs Theater strategy and also discusses briefly the utilization of Readers Theater strategy to EFL students.